THE EFFECT OF USING POWERPOINT MODIFIED PICTURES IN WRITING DESCRIPTIVE TEXT TO THE EIGHTH GRADE STUDENTS OF SMPN 22 KOTA BENGKULU IN 2016/2017 ACADEMIC YEAR - Tri Susilo; Kasmaini .; Indah Damayanti (Universitas Bengkulu, 2018)
This study aimed at investigating the effect of using powerpoint modified pictures as a media in teaching writing descriptive text. The population of this study was all the students of eighth-grade students of SMPN 22 Kota Bengkulu in academic year 2016/2017 with the total number of population 66 students. The sample of this research was taken by using purposive sampling. By using that technique, 42 students were taken as the samples. The samples divided into two groups, experimental and control group. The instrument employed in this study was writing tests. The pre-test was conducted before giving treatments in order to know the scores of both groups. After giving some treatments to the experimental and control group, the post-test was held to both groups. Based on the data analysis of the post-test, it was found that t-count > t-table (4.66 > 2.021). This finding indicated that there was a significant difference between the experimental and control group scores. It means that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. In other words, powerpoint modified pictures had a significant effect on students’ writing ability. The use of powerpoint modified pictures could increase students’ writing ability especially in descriptive text. Therefore, this technique can be applied by the teacher as a teaching aid in descriptive text’s writing.